Court Enforcement, Bank Loans, and Firm Investment: Evidence from a Bankruptcy Reform in Brazil * - Ponticelli, Jacopo; Alencar, Leonardo S. (Quarterly Journal of Economics, 2016)
Abstract We exploit variation in the congestion of civil courts across Brazilian municipalities, together with a bankruptcy reform increasing secured creditors’ protection, to estimate the effect of enforcement on firm access to finance, investment, and size. We find that firms operating in municipalities with less congested courts experienced a larger increase in the use of secured loans, as well as a larger increase in investment and value of output in the years after the reform. To establish the direction of causality, we use an instrumental variable strategy that exploits Brazilian state laws on judicial organization, and focus on differences in court congestion across otherwise similar neighboring municipalities located across judicial district borders within the same state. The evidence indicates that differences in court enforcement affect the impact of financial reform on firm access to finance, investment, and size.